E-aviation speaking preparation test for aviation vocational school - Sylvia, Tiara; Rochmawati, Laila; Novalina, Susi Diriyanti; Saragih, Nisa Azhari; Rosyid, Harunur (Institute of Advanced Engineering and Science, 2024)
An e-module aviation speaking preparation test has been developed to support cadets of aviation vocational schools in preparing English language proficiency tests. This research aimed to assess whether there was an improvement in cadets’ aviation speaking preparation test scores after studying the E-Module. A sample of 120 cadets participated in the study to examine the effect of E-Module aviation speaking preparation test to enhance aviation speaking abilities. The validation test score of 89.5% indicates that the E-Module aviation speaking preparation test is very valid for usage. Independent sample T-test results revealed differences between pretest and posttest scores of the e-module aviation speaking preparation test for cadets at both aviation polytechnics. Paired T-test results indicated that cadets who utilized the E-Module achieved higher learning with a significance value of (0.000)<α (0.05). The correlation between pretest and posttest scores and the learning outcomes of the E-Module aviation speaking preparation test showed a relatively high level of correlation, with a coefficient of 0.480 and a significance value of Sig (2-tailed=0.000)<½ α (0.025). These findings suggest that the E-Module aviation speaking preparation test effectively enhances the aviation English speaking abilities of cadets.